Enhancement mechanism of biogas potential from lignocellulosic substrates in the ensiling process via acid-based hydrolysis and biological degradation. (15th October 2021) - Sun, Hui; Li, Juan; Cui, Xian; Stinner, Walter; Guo, Jianbin; Dong, Renjie
Abstract: This study investigated the effects of acid-based hydrolysis and biological degradation during the ensiling process as a pretreatment for biogas production. In nine separate treatments, lactic, acetic, and butyric acid were added to wilted maize stover at 20, 50, and 80 g/kg dry matter (DM) and then ensiled for 60 d. Synergetic effects of acid-based hydrolysis and biological degradation were observed in the three treatments with an organic acid addition of 20 g/kg of DM, which resulted in a lignocellulose degradation rate (LDR) of 26%–31% and a biomethane potential (BMP) increase of 10%–13% with respect to that of the raw material. However, in the treatments with an organic acid addition of 80 g/kg of DM, although the biological degradation was almost completely inhibited, the LDR was still 20%–24% and the BMP increased by 6%–8% with respect to that of the raw material. These results showed that acid-based hydrolysis played a dominant role in increasing the BMP (accounting for 55%–65%) and that biological degradation was able to further enhance biodigestibility. Therefore, the authors suggest that an ensiling regulation strategy, as opposed to a single enhancement, may be preferable for synergistically strengthening the organic acid fermentation and microbial activity during ensiling to achieve efficient biogas production. Highlights: Acid-based hydrolysis and biological degradation in ensiling process were studied. Synergetic effects of acid-based hydrolysis and biological degradation were proved. Acid-based hydrolysis played a crucial role in biodigestibility and BMP increase. The biological degradation could further improve biodigestibility and BMP. Enhancing acid fermentation and microbe activity are advised for biogas production.